Analisis Kadar Vitamin C Pada Buah Jeruk Nipis (Citrus aurantifolia Swing.) dan Jeruk Manis (Citrus sinensis) menggunakan Titrasi Iodometri - Farida Ariani; Lalu Busyairi Muhsin (Department of Pharmacy, Bumigora University, 2023)
Vitamins are a class of organic compounds that have a very important role for growth, maintenance of health, and other bodily functions so that the metabolism runs normally. There are lots of vitamins both of natural origin and those synthesized in the laboratory. One of them is vitamin C, this study aims to determine the levels of vitamin C (ascorbic acid) in samples of citrus fruit, lime and vitacimin by iodimetric titration. Redox titrations are titrations that involve oxidation and reduction processes. These two processes always occur simultaneously. In redox titrations usually use potentiometric to detect the end point. To determine vitamin C levels, the redox titration method used is direct titration using iodine. Iodine will oxidize compounds that have a smaller reduction potential than iodine. Based on the experiments conducted on the vitamin C test, it can be concluded that the determination of vitamin C levels by iodometric titration can be carried out on the principle of oxidation reduction. Vitamin C levels were obtained by iodometric titration method first which was carried out by diluting oranges, limes and vitamin C by 0.0006%, 0.0006287%, 0.000787%. In the second method without dilution, the concentration of vitamin C in oranges and limes is 0.03165%, 0.0 9%.